Financial Decisions in Family Business: The Application of Financial Growth Cycle and The Theory of Planned Behavior - Nurchayati, Nurchayati; Suprantiningrum, Rr.; , Muchayatin; Soegiastuti, Janti (School of Business, IPB University (SB-IPB), 2024)
Family businesses are influenced by economic and non-economic factors when it comes to making decisions, including financing decisions for business growth. In particular, individual financial attitudes could greatly affect financial behavior in family firms. This study explored the relationship between access to information, external sources, family norms, and experience in influencing financing decisions for family business growth. The study collected data through questionnaires from 153 managers/owners in micro, small, and medium enterprises in Semarang. It used a quantitative method with regression analysis techniques with the Structural Equation Modeling (SEM) using AMOS software. The study found that information access (S.E.=0.078; p-value=0.001), external sources (S.E.= 0.055; p-value=0.000), family norms (S.E.= 0.069; p-value=0.000) had significant effects on experience. Moreover, financing decisions were influenced by family norms (S.E.= 0.072; p-value=0.000), and experience (S.E.= 0.089; p-value=0.001). The results also show that experience could mediate the relationship between access to information and external sources with financing decisions. Based on these findings, family businesses need to consider these factors when making financing decisions to succeed carefully. This study provides important insights for family businesses looking to make informed and effective decisions regarding financing their growth. Keywords: financing decisions, family business, financial growth cycle, theory of planned behavior